Group Gap Acceptance: A New Method to Analyze Driver Behavior and Estimate the Critical Gap at Multilane Roundabouts - Khaled Shaaban; Hassan Hamad (Journal of Advanced Transportation)
The operations of multilane roundabouts, especially three-lane roundabouts, are unique and more complicated than any other type of roundabouts. This study aims to analyze driver behavior and estimate the critical gap at three-lane roundabouts. Video data were collected at two roundabouts. The analysis identified a pattern of group gap acceptance, where vehicles entering the roundabout from different lanes moved in groups during the same gap. In this case, the decision of vehicles entering from outside lanes greatly depended on the gap acceptance decision of vehicles in the inside lane. Analysis showed that the vast majority of the vehicles accept the gap in groups and the critical gap was estimated accordingly. The study provides a new explanation for the operation at multilane roundabouts. The use of this simple method is recommended when estimating critical gaps for multilane roundabouts.